Discovery of the Qinghe fault, the inner part of the Weihe graben, central China, and its geological significance - Li, Wei; Feng, Xijie (Frontiers in Earth Science, 2023)
The Weihe graben is an active Cenozoic continental rift with frequent seismic activity. The previous work focused on the graben boundary faults, but less work has been conducted on the faults in the internal graben. The Weihe basin is an economically developed and densely populated area with frequent historical earthquakes. Therefore, identifying these potential risks is significant for the evaluation of regional seismic hazards and to understand the evolution of continental rifts. Prior work used oil exploration methods to document a fault (we named it “Qinghe fault”) in the Qinghe river area of Sanyuan County, north of Xi’an. But the shallow structure and activity was not clear. Therefore, we carried out shallow seismic detection and borehole exploration, as well as a geological survey in the area. Based on seismic reflection profile and boreholes, the Qinghe fault is the main fault and with other secondary faults, together they constitute a typical Y-shaped structure, with a fracture zone width ~ 4 km. Combined with the field survey, we provide evidence that the Qinghe fault is a Holocene active fault and capable of earthquakes of magnitude 5.2-5.5. The discovery of the Qinghe fault shows that the Weihe rift is active, and the faults inside the rift play an important role in tectonic deformation.